Social inclusion of clients treated for substance abuse in Sweden in the 1980s: A 27-year follow-up. Issue 4 (August 2019) - von Greiff, Ninive; Skogens, Lisa; Berlin, Marie
Aim: To investigate social inclusion/exclusion in terms of criminality, substance abuse and participation in the labour market in clients treated for substance abuse in Sweden in the 1980s during a follow-up period of 27 years. Method: SWEDATE data are used for background information on the clients. The data were collected through interviews with clients registered for treatment in 31 in-patient treatment units in 1982 and 1983. Data on labour market status, education and medication related to drugs were collected from public registers. The study population consisted of 1132 individuals, who were followed from the year after exiting from treatment (Year 1) until the end of the follow-up (December 2013). Results: Among those who survived, the women seem to have succeeded better in terms of social inclusion both at an aggregated level and when the individual pathways were followed during the follow-up period. When comparing pathways between adverse and non-adverse groups during the follow-up period the results show movements from being adverse to non-adverse but also the opposite. In the last follow-up in 2013, the majority of the clients defined as non-adverse for the last nine years were in some way established in the labour market (including studies). In total, about two fifths of the group were in some way established in the labour market. Conclusions: The fairly high proportion of clients moving between being adverse and non-adverse during the follow-up might support the perspective suggesting that dependence should not be considered as chronic.